Association between circadian syndrome and gallstones in US adult: a cross-sectional study of NHANES 2017–2020 - Liang, Fenping; Qin, Tianyan; Hao, Zhuang; Zheng, Ya; Zhou, Yongning (BMC gastroenterology, 2024)
The circadian syndrome is linked with chronic diseases such as stroke, kidney stones, and overactive bladder. However, the relationship between circadian syndrome and gallstones is poorly understood. In this study, we aim to investigate whether circadian syndrome is associated with gallstones in a population-based study. Using data from the National Health and Nutrition Examination Survey (NHANES) database spanning from 2017 to 2020, a cross-sectional study with 2913 participants was performed to assess the relationship between circadian syndrome and gallstones. Univariate and two adjusted multivariate regression models were used to examine the connection between circadian syndrome and gallstones incidence. Smoothed curve fitting using the generalized additive model (GAM) was used to describe the nonlinear relationship. Subgroup analyses were also performed to investigate potential variations in the relationship between circadian syndrome and the risk of developing gallstones. The findings indicated a positive association of circadian syndrome with gallstones, with model 2 showing a 117% increase in risk (OR = 2.17, 95% CI 1.43, 3.29). In model 3, the incidence of gallstones increased by 76% (OR = 1.76, 95% CI 0.91, 3.43). However, there was no significant relationship between the number of circadian syndrome components and the risk of gallstones. Smooth curve fitting based on the GAM further demonstrated linear relationships between CircS and the risk of gallstones. Subgroup analyses further demonstrated statistically significant associations between circadian syndrome and the prevalence of gallstones among individuals who were non-smokers. Circadian syndrome was positively associated with the prevalence of gallstones, particularly among non-smoking participants.